Occupational health and safety of the frontline healthcare workers in Nepal in COVID-19 pandemic - Joshi, Sunil Kumar (International Journal of Occupational Safety and Health, 2021)
Occupational health and safety (OHS) is essential for every professional especially healthcare workers who work day and night serving patients. According to the WHO, health workers should not face any kind of workplace violence during their professional activities. Attention should also be paid to the mental and psychological health of healthcare workers and their protection should be of paramount importance. OHS related policies, rules and regulations have been formulated in Nepal. According to the law, the responsibility of the OHS of the employees has to be taken by the concerned organization. In Nepal, during the COVID-19 pandemic, health workers have to take the risk of infecting themselves while providing care for the patients. This has led to the infection of thousands of health workers and we have also lost quite a few healthcare workers in the line of duty in Nepal. On one hand, there is a psychological fear of acquiring COVID-19 infection in healthcare workers despite adopting health and safety measures, while on the other hand, in case of infection they will have to pay for the treatment from their own pockets. Sometimes ICU and ventilator services are not available not only in their working hospital but also in government referral health institutions which have given rise to incidences that healthcare workers themselves have to be admitted to other hospitals for the treatment. In such a situation, not just mental but also a financial burden has been added to the healthcare workers.